„A co na owo zdanie, że kobieta niezamężna marnieje, to nigdy się nie zgodzę”, czyli rzecz o Krystynie Klementyny z Tańskich Hoffmanowej oraz o jej autorce (wybrane aspekty kulturowe) - Stankiewicz-Kopeć, Monika (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
This article brings to light the novel Krystyna (Lipsk, 1841), a work known to very few literary historians despite the fact that it was written by Klementyna née Tańska Hoffmanowa, one of the most famous and influential Polish novelists of the first half of the 19th century. In it, the author defended unmarried women and demonstrated that spinsterhood could be simultaneously socially beneficial and life-satisfying for the woman in question. In this respect, Krystyna, whose ideological message stands out among the novels of its time, constitutes a definitive voice in the debate surrounding spinsterhood in 19th-century Polish literature and as such may be regarded as a pioneering work in the defense of single women (including those who intentionally chose not to marry). This analysis also touches on important social issues of the first half of the 19th century. It draws attention to issues in women’s everyday life, their privacy (primarily those related to family and social relationships, and the choice of a husband), and the role of women as custodians of family and national traditions. Above all, however, it addresses matters related to the experiences of unmarried women. The model of a free woman proposed by Hoffmanowa in Krystyna reconciled old (pre-partition) tendencies deeply rooted in Polish tradition with modern (Enlightenment) influences, while also taking into account new demands that emerged during a period of political subjugation.